Energetic evaluation of binding modes in the C3d and Factor H (CCP 19‐20) complex. (11th March 2015) - E. S. Harrison, Reed; Gorham, Ronald D.; Morikis, Dimitrios
Abstract: As a part of innate immunity, the complement system relies on activation of the alternative pathway (AP). While feed‐forward amplification generates an immune response towards foreign surfaces, the process requires regulation to prevent an immune response on the surface of host cells. Factor H (FH) is a complement protein secreted by native cells to negatively regulate the AP. In terms of structure, FH is composed of 20 complement‐control protein (CCP) modules that are structurally homologous but vary in composition and function. Mutations in these CCPs have been linked to states of autoimmunity. In particular, several mutations in CCP 19‐20 are correlated to atypical hemolytic uremic syndrome (aHUS). From crystallographic structures there are three putative binding sites of CCP 19‐20 on C3d. Since there has been some controversy over the primary mode of binding from experimental studies, we approach characterization of binding using computational methods. Specifically, we compare each binding mode in terms of electrostatic character, structural stability, dissociative and associative properties, and predicted free energy of binding. After a detailed investigation, we found two of the three binding sites to be similarly stable while varying in the number of contacts to C3d and in the energetic barrier to complex dissociation. These sites are likely physiologically relevant and may facilitate multivalent binding of FH CCP 19‐20 to C3b and either C3d or host glycosaminoglycans. We propose thermodynamically stable binding with modules 19 and 20, the latter driven by electrostatics, acting synergistically to increase the apparent affinity of FH for host surfaces.